COVID-19 VOCABULARY: LEARNING AND UNDERSTANDING - Santy Christinawati; Wahyu Trimastuti (Jurnal Sastra - Studi Ilmiah Sastra, 2021)
Vocabulary represents one of most important skills necessary for teaching and learning a foreign language. It is the basis for the development of all the other skills: reading comprehension, listening comprehension, speaking, writing, spelling and pronunciation. Vocabulary is the main tool for the students in their attempt to use English effectively. Both teacher and students in this era have to provide their ability to update and enlarge new vocabularies, especially in. pandemic Covid -19 era. The coronavirus pandemic has brought not only serious disruption and change to countries across the world but also a new range of terminology to help describe the disease. The era will not be under control until there is at least a working vaccine. The writers have tried to enlarge the English vocabulary related to Covid-19 matter.